Relevansi Penundaan Pemilihan Umum Tahun 2024 dalam Perspektif Hukum Tata Negara Darurat - Denis - Kurniawan (Badan Strategi Kebijakan Hukum, 2023)
Discourse on postponing the elections in 2024 was circulated amid the ongoing Corona Virus Disease 2019 (Covid-19) Pandemic, which conceptually could be classified as a civil emergency in Indonesia. The discourse was brought up by a certain group of political elites and received various responses in the community, from those who approved to those who rejected the idea. This paper describes the implementation of the 2024 elections in the context of the state of emergency, as a branch of the scientific study of constitutional law that discusses the state when it is faced with abnormal conditions, aka emergencies due to dangers that threaten the continuity of the nation and state. This paper uses normative legal research conducted using a statutory and conceptual approach which will later assess whether the postponement of the election can be justified from the point of view of the state of emergency, and by looking at the implications of the current danger of Covid-19 supported by policies that there is from the government, as well as the election management body itself, namely the General Elections Commission.